Green mixed surfactant nanoemulsion formulation of cytokinin NPK fertilizer for cultivating ceylon spinach (Basella alba) - Shee, Eyvonne Yu Qian (2023)
The soil applied granular and liquid fertilizers contain three important nutrients which are nitrogen, phosphorus and potassium. Plants only absorb 10-40% of the fertilizers applied while 60-90% of the fertilizers is lost due to washed off from the ground and leaching into the waterways during rain, therefore cause eutrophication of water bodies. In order to solve these problems, the nanoemulsion formulations of liquid fertilizer that absorb through leaves into the plants are capable of maximizing nutrients uptake via foliar spray. This study aims to formulate nanoemulsion cytokinin NPK fertilizer and investigate the nanoemulsion system with cytokinin NPK fertilizer on the cultivation of Ceylon spinach (Basella Alba). The phase behaviours of emulsions were studied using palm oil fatty methyl ester 1218K and the mixed surfactants, Tween 80 and alkyl polyglucosides and water. The emulsions of transparent isotropic phase were obtained at the surfactant:oil ratio of 9:1 and mixed surfactant ratio of 9:1 and 8:2. These stable emulsions were added into the mixed cytokinin NPK fertilizer through phase inversion composition iii (PIC) method to produce nanoemulsion formulation. The nanoemulsion formulations of cytokinin NPK fertilizer were stable under heat stress, 54℃ for two weeks. The result of High Resolution Transmission Electron Microscope (HRTEM) indicates spherical particles are observed in the nanoemulsion formulations. The nanoemulsion were incorporated well into the cytokinin NPK fertilizer solution. The particle sizes are in the range of 20 nm to 250 nm. The formulated nanoemulsion fertilizers were assessed by the measurement of chlorophyll content, total phenolic content, fresh mass, surface area of leaves and the number of leaves of Ceylon Spinach. The plants that treated with cytokinin nanoemulsion fertilizers grow the healthiest which is indicated by 35.0 SPAD of chlorophyll content, 10.4459 mgGAE/L of total phenolic content, 4.0 leaves per plant, 2.6715 g of fresh weight and 12.44 cm2 surface area of leaves in comparison to the non-formulated cytokinin NPK fertilizer.